Mild cognitive impairment is associated with low copy number of ribosomal genes in the genomes of elderly people - Veiko, Natalia N.; Ershova, Elizaveta S.; Veiko, Roman V.; Umriukhin, Pavel E.; Kurmyshev, Marat V.; Kostyuk, Georg P.; Kutsev, Sergey I.; Kostyuk, Svetlana V. (Frontiers in Genetics, 2022)
Introduction: Mild cognitive impairments (MCI) accompanying aging are associated with oxidative stress. The ability of cells to respond to stress is determined by the protein synthesis level, which depends on the ribosomes number. Ribosomal deficit was documented in MCI. The number of ribosomes depends, together with other factors, on the number of ribosomal genes copies. We hypothesized that MCI is associated with low rDNA CN in the elderly person genome. Materials and Methods: rDNA CN and the telomere repeat (TR) content were determined in the DNA of peripheral blood leukocytes of 93 elderly people (61-91 years old) with MCI and 365 healthy volunteers (16 – 91 years old).The method of non-radioactive quantitative hybridization of DNA with biotinylated DNA probes was used for the analysis. Results: In the MCI group, rDNA CN (mean 329 ± 60; median 314 copies, N=93) was significantly reduced (p<10-15) compared to controls of the same age with preserved cognitive functions (mean 412 ± 79; median 401 copies, N=168) and younger (16-60 years) control group (mean 426 ± 109; median 416 copies, N=197). MCI is also associated with a decrease in TR DNA content. There is no correlation between the content of rDNA and TR in DNA, however, in the group of DNA samples with rDNA CN >540, TR content range was significantly narrowed compared to the rest of the sample. Conclusion: Mild cognitive impairment is associated with low ribosomal genes copies in the elderly people genomes. A low level of rDNA CN may be one of the causes of ribosomal deficit that was documented in MCI. The potential possibilities of using the rDNA CN indicator as a prognostic marker characterizing human life expectancy are discussed.